No correlation between plasma levels of vascular endothelial growth factor or its soluble receptor and acute mountain sickness - Schommer, Kai; Wiesegart, Neele Ruth; Dehnert, Christoph; Mairbäurl, Heimo; Bärtsch, Peter (High altitude medicine & biology, 2011)
No correlation between plasma levels of vascular endothelial growth factor or its soluble receptor and acute mountain sickness. High Alt. Med. Biol. 12:323-327.—Increased plasma levels of vascular endothelial growth factor (VEGF) due to lower levels of its soluble receptor (sFlt-1) had been suggested to cause vasogenic brain edema and thereby to cause the symptoms of acute mountain sickness (AMS). We tested this hypothesis after active ascent to high altitude. Plasma was collected from 31 subjects at low altitude (100 m) before (LA1) and after (LA2) 4 weeks of aerobic exercise training in normobaric hypoxia or normoxia, and one night after ascent to high altitude (4559 m). Training modalities (hypoxia or normoxia) did not influence VEGF- and sFlt-1-levels. Therefore, data of both training groups were analyzed together. After one night at 4559 m, 18 subjects had AMS (AMS+), 13 had no AMS (AMS−). In AMS+ and AMS−, VEGF was 110±75 (SD) pg/ml vs. 104±82 (p=0.74) at LA1, 63±40 vs. 73±50 (p=0.54) at LA2, and 88±62 vs. 104±81 (p=0.54) at 4559 m, respectively. Corresponding values for sFlt-1 in AMS+ and AMS− were 81pg/ml±13.1 vs. 82±17 (p=0.97), 79±11 vs. 80±16 (p=0.92) and 139±28 vs. 135±31 (p=0.70), respectively. Absolute values or changes of VEGF were not correlated and those of sFlt-1 slightly correlated with AMS scores. These data provide no evidence for a role of plasma VEGF and sFlt-1 in the pathophysiology of AMS. They do, however, not exclude paracrine effects of VEGF in the brain.
Gesehen am 26.10.2022